Mental Representation of Stimuli Austrian and Swiss Humour - Оксана Зубач (Психолінгвістика, 2025)
The purpose of the study is to analyse linguistic consciousness, the specificity of cross-cultural communication, the role of humour as a social product of language, and culture and a person’s mentality identification, which is formed under the influence of psycholinguistic elements of perceiving the world and acquiring knowledge about it. Special attention has been given to studying the specificity of perceiving the Austrian and Swiss humour and their identification in the German-speaking space through the stimuli Österreichischer Humor and Schweizer Humor.